The Influence Of Socioeconomic Factors On Sustainable Pepper Agroforestry Systems - Annisa Ambar Justitia; Yudi Sapta Pranoto; Rostiar Sitorus (INDONESIAN JOURNAL OF SMALL SCALE FARMING, 2025)
BACKGROUND AND OBJECTIVES: Pepper production in Central Bangka Regency declined from 2019 to 2023 because pepper cultivation practices have not yet been implemented according to GAP (Good Agricultural Practices). The agroforestry system is one approach to addressing this issue. However, many pepper farmers have not widely applied this system, so it is necessary to understand farmers' attitudes toward the successful implementation of a sustainable pepper agroforestry system. This study aims to describe pepper farmers' attitudes toward the agroforestry system as a solution for sustainable agriculture and analyze the socioeconomic factors influencing their adoption of a sustainable pepper agroforestry system in Central Bangka Regency. METHODS: The research method used is quantitative with a descriptive approach and multiple linear regression analysis. Primary data were collected through questionnaires from 105 pepper farmers selected by purposive sampling. FINDINGS: The results show that the attitude of pepper farmers towards the agroforestry system falls into the ‘agree’ category, with an average variable achievement rate of 80.27%. The cognitive and conative attitude components fall into the strongly agree category, while the affective component falls into the agree category. Socioeconomic factors have a significant simultaneous effect on the attitude of pepper farmers in implementing a sustainable pepper agroforestry system, contributing 64.2%. Partially, the variables of age, formal education, income, and culture have a significant effect on the attitude of pepper farmers in implementing a sustainable pepper agroforestry system, while the variables of non-formal education and farming experience do not have a significant effect. CONCLUSION: The attitude of pepper farmers towards the agroforestry system is in the strongly agree category, consisting of cognitive, affective, and conative components. Socioeconomic factors simultaneously have a significant effect on the attitude of pepper farmers in implementing a sustainable pepper agroforestry system. Meanwhile, partially, the socioeconomic factor variables that influence the attitude of pepper farmers include age, formal education, income, and culture.